KARAKTERISTIK KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS X SMA ADABIAH PADANG - Fitri, Rika; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT This article expressed the characteristics of the sentences in the exposition text of X grade students of Adabiah Padang High School. Two purposes of this study, the first one was to describe the sentence structure (subject, predicate, object, and description) contained in the text of exposition written by X grade. The second aim was to describe the type of sentence based on the number of clauses in the sentence (single  and compound sentences) contained in the text of exposition of X grade. The type of this research was  a qualitative using descriptive methods. This research was conducted at Adabiah Padang High School, especially in the  X grade which the total was 124 students. The entry of this study was the writing of exposition text by X grade in terms of sentence characteristics (sentence structure and type of  sentence). Data discussed was qualitative. The data analyzed in the form of sentence characteristics (structure and types of sentences) contained in the exposition text of the work of  X grade. Source of the data in this research was  the text of exposition written by X grade. There were two research findings which the first was  the sentence structure that was widely used by  X grade was  S + P + O pattern, the total was 88 sentences from 152 sentences studied. Second, the type of sentences used by X grade were single sentence types, which the amount was 140 sentences from 152 sentences studied. Kata kunci: Karakteristik, Kalimat, Teks Eksposisi